Decree no. 50 of the year 2014 concerning the issue of the financial and administrative regulations for the employment and care units of irregular labor (seasonal and temporary construction and agricultural workers and the like ) = قرار وزارة الهجرة والقوى العاملة رقم 50 لسنة 2014 بشأن إصدار اللائحة المالية والإدارية لوحدات تشغيل ورعاية العمالة غير المنتظمة (عمال المقولات والزراعة الموسميين والمؤقتين ومن في حكمهم). - Egypt. financial and administrative regulations for the employment (2025)
Ministry of manpower and immigration decree no. 50 of the year 2014 concerning the issue of the financial and administrative regulations for the employment and care units or irregular labor – The Arab Republic of Egypt Ministry of manpower and immigration central committee for the employment of irregular labor financial and administrative regulations for the employment and care units of irregular seasonal and temporary labor 2014 – section 1: definitions and general provisions – section 2: the advisory committee for local employment – section 3: responsibilities of the irregular labor unit – section 4: survey, record and follow up of the employment of the seasonal and temporary construction and agriculture workers and the like. وزارة القوى العاملة والهجرة قرار رقم 50 لسنة 2014 بشأن إصدار اللائحة المالية والإدارية لوحدات تشغيل ورعاية العمالة غير المنتظمة (عمال المقاولات والزراعة الموسميين والمؤقتين ومن فى حكمهم) – جمهورية مصر العربية وزارة القوى العاملة والهجرة اللجنة المركزية لتشغيل العمالة غير المنتظمة اللائحة المالية والإدارية لوحدات تشغيل ورعاية العمالة غير المنتظمة الموسميين والمؤقتين 2014 – القسم الأول التعاريف والأحكام العامة – القسم الثانى اللجنة الاستشارية للتشغيل المحلى – القسم الثالث اختصاصات وحدة العمالة غير المنتظمة – القسم الرابع حصر عمال المقاولات والزراعة ومن فى حكمهم الموسميين والمؤقتين وتسجيلهم ومتابعة تشغيلهم